The Relationship between Culture and Food Abstinence Behaviour among Postpartum Mothers in the Working Area of Padang Tiji Health Center, Padang Tiji District - Fauziah Fauziah; Nursinah Nursinah; Muzia Ulfa (Universitas Serambi Mekkah, 2022)
Health development as one of the national development goals has been focused on building awareness, willingness and ability of people to live a healthy lifestyle and achieve optimal health status. Management of various governmental and community resources is needed to achieve the goasl and to provide efficient, quality and affordable health services. The purpose of this study was to determine the relationship between culture and food abstinence behavior during the postpartum period in the Padang Tiji Health Center Work Area, Padang Tiji District, Pidie Regency. Abstinence of food is not advised on postpartum mothers because it can slow down the healing process of perineal sutures. Instead, postpartum mothers are recommended to eat food in the right quality and quantity, particulary food containing protein. There were two variables in this study, namely culture and food abstinence behavior. The samples of this study were all postpartum mothers in the Padang Tiji Health Center Work area, totaling 32 people. This research was analytical with the crosssectional design. The results revealed that there is a significant relationship between culture and food taboo behavior during the puerperium. The majority of respondents (62.5%) said that they abstained from food. The results also showed that a good culture leads to a more positive behavior (46.9%). It is thus expected that all mothers in the Padang Tiji Health Center Work area can gain updated information on food taboos during the puerperium. Keywords: Behavior, Culture, Dietary Restrictions, Postpartum Mothers.